2006
DOI: 10.1073/pnas.0510561103
|View full text |Cite
|
Sign up to set email alerts
|

Development of CD4+T cells expressing a nominally MHC class I-restricted T cell receptor by two different mechanisms

Abstract: Most ␣␤ T cells belong to one of the two lineages defined by the mutually exclusive expression of CD8 or CD4 coreceptors, which bind MHC class I and class II molecules, respectively. Because the binding of the coreceptors to MHC molecules stabilizes weak interactions between TCRs and peptide-MHC (pMHC) complexes, CD8 ϩ T cells are MHC class I-restricted whereas CD4 ϩ T cells are MHC class II-restricted. The concordance of CD4 or CD8 lineage development with specificity for class I or II MHC is established duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 55 publications
4
16
0
Order By: Relevance
“…Similar proportions of GCAA peptide-speciWc T cell clones were derived from CD8 + (18%) and CD4 + (15%) [5,12,37,48]. Accordingly, in our present studies we have found that a restricted number (one or two per patient) of speciWc CD4 + T cell clones showed an HLA class I-restricted response to GCAA peptides.…”
Section: Discussionsupporting
confidence: 81%
“…Similar proportions of GCAA peptide-speciWc T cell clones were derived from CD8 + (18%) and CD4 + (15%) [5,12,37,48]. Accordingly, in our present studies we have found that a restricted number (one or two per patient) of speciWc CD4 + T cell clones showed an HLA class I-restricted response to GCAA peptides.…”
Section: Discussionsupporting
confidence: 81%
“…2 and data not shown) (14) and (ii) there are differences in the intensity with which various TCRs react with self-pMHC complexes. Thus, 2C T cells and thymocytes recognize ubiquitously expressed mitochondrial peptide-K b complexes (35)(36)(37)(38), and, like male-specific HY TCR ϩ cells in male mice (39), they may be more reactive with self-pMHC than T cells that express other TCR transgenes (5).…”
Section: Discussionmentioning
confidence: 99%
“…At least two mechanisms contribute to these mismatches (4,5). In TCR-transgenic mice that express recombination-activating genes (RAG ϩ ), the absence of allelic exclusion of the TCR ␣ genes can lead to expression in the same T cell of two TCRs, the transgenic ␣␤ TCR and another TCR, consisting of the transgenic TCR ␤ chain and an endogenous TCR ␣ chain.…”
mentioning
confidence: 99%
See 2 more Smart Citations